Application of community treatment orders (CTOs) in adults with intellectual disability and mental disorders. Issue 4 (6th July 2015) - Gupta, Jaya; Hassiotis, Angela; Bohnen, Ingrid; Thakker, Yogesh
Abstract : Purpose: – The purpose of this paper is to explore use of community treatment orders (CTOs) in adults with intellectual disability (ID) and mental health problems across England and Wales. Design/methodology/approach: – A web-based exploratory survey was sent to 359 consultants on the database of the Faculty of the Psychiatry of ID, Royal College of Psychiatrists who had declared ID as their main speciality. Socio-demographic details of responding consultants, clinical characteristics of adults with ID on CTO, subjective views of consultants on using CTOs in people with ID were collected and analysed. Findings: – In total, 94 consultant questionnaires were returned providing information on 115 patients detained under CTO. More than 75 per cent of the respondents had used CTO in their clinical practice. Patients subject to CTO were generally young, white males with mild ID and living in supported accommodation. CTOs were primarily used in situations of non-engagement (52.2 per cent), non-compliance with medication (47 per cent) or non-compliance with social care supports (49.6 per cent). Practical implications: – Responding consultants expressed concerns about encroachment of civil liberties and ethics of using CTOs in people with ID who may lack capacity and stressed that decision to use CTOs needs to be therefore done on individual basis. Originality/value: – This is the first national study to examine the practice of applying CTOs in adults with ID and mental disorders. Current practice is based on evidence from research done in adults with normal intelligence. Further research is needed to investigate the utility of CTOs in routine clinical practice in adults with ID and mental disorders.